2021
DOI: 10.1371/journal.ppat.1009835
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated action of multiple transporters in the acquisition of essential cationic amino acids by the intracellular parasite Toxoplasma gondii

Abstract: Intracellular parasites of the phylum Apicomplexa are dependent on the scavenging of essential amino acids from their hosts. We previously identified a large family of apicomplexan-specific plasma membrane-localized amino acid transporters, the ApiATs, and showed that the Toxoplasma gondii transporter TgApiAT1 functions in the selective uptake of arginine. TgApiAT1 is essential for parasite virulence, but dispensable for parasite growth in medium containing high concentrations of arginine, indicating the prese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…This hypothesis was supported in a recent publication in which TgApiAT6-1 was identified as the transporter that mediates TgApiAT1-independent L-arginine uptake in T. gondii [75]. Specifically, two parallel studies on TgApiAT6-1 have demonstrated that this protein is a general cationic amino acid transporter that mediates both the high-affinity uptake of L-lysine and the low-affinity uptake of L-arginine [75,76]. Furthermore, TgApiAT6-1 is the sole L-lysine transporter in T. gondii, explaining the indispensability reported in the corresponding gene [76].…”
Section: Amino Acid Transportersmentioning
confidence: 58%
See 3 more Smart Citations
“…This hypothesis was supported in a recent publication in which TgApiAT6-1 was identified as the transporter that mediates TgApiAT1-independent L-arginine uptake in T. gondii [75]. Specifically, two parallel studies on TgApiAT6-1 have demonstrated that this protein is a general cationic amino acid transporter that mediates both the high-affinity uptake of L-lysine and the low-affinity uptake of L-arginine [75,76]. Furthermore, TgApiAT6-1 is the sole L-lysine transporter in T. gondii, explaining the indispensability reported in the corresponding gene [76].…”
Section: Amino Acid Transportersmentioning
confidence: 58%
“…However, TgApiAT1 is dispensable for parasite growth in a medium containing high concentrations of L-arginine, suggesting the pres-ence of at least one other L-arginine transporter. This hypothesis was supported in a recent publication in which TgApiAT6-1 was identified as the transporter that mediates TgApiAT1-independent L-arginine uptake in T. gondii [75]. Specifically, two parallel studies on TgApiAT6-1 have demonstrated that this protein is a general cationic amino acid transporter that mediates both the high-affinity uptake of L-lysine and the low-affinity uptake of L-arginine [75,76].…”
Section: Amino Acid Transportersmentioning
confidence: 70%
See 2 more Smart Citations
“…the parasite sensing conditional changes. This expands on recent evidence that metabolic pathways are in fact essential only when parasites are grown in low-nutrient in vitro conditions [6][7][8][9]. Here we review some of the major metabolic pathways on which T. gondii depends for survival, and we interrogate the metabolic flexibility in the context of nutrient availability to explore the physiological relevance of in vitro systems during infection.…”
Section: The Versatility Of the Toxoplasma Parasitementioning
confidence: 85%